化简 (x^2-2xy+y^2-1)/(x-y-1)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 01:31:04
化简(x^2-2xy+y^2-1)/(x-y-1)化简(x^2-2xy+y^2-1)/(x-y-1)化简(x^2-2xy+y^2-1)/(x-y-1)x^2-2xy+y^2-1=(x-y)^2-1^2
化简 (x^2-2xy+y^2-1)/(x-y-1)
化简 (x^2-2xy+y^2-1)/(x-y-1)
化简 (x^2-2xy+y^2-1)/(x-y-1)
x^2-2xy+y^2-1
=(x-y)^2-1^2
=(x-y+1)(x-y-1)
所以原式=(x-y+1)(x-y-1)/(x-y-1)=x-y+1
X-y+1
x-y+1
(x^2-2xy+y^2-1)/(x-y-1)
=((x-y)^2-1)/(x-y-1) =(x-y-1)(x-y+1)/(x-y-1) =x-y+1
(x^2-2xy+y^2-1)/(x-y-1)
=[(x-y)^2-1]/(x-y-1)
=(x-y+1)(x-y-1)/(x-y-1)
=(x-y+1)
化简!1、(x^2-xy)+xy+y^2 2、3(x^2-xy)-xy+y^2
1.(xy-1)^2-(x+y-2xy)(2-x-y)2.(x+y)(x+y+2xy)+(xy-1)(xy+1)
分解因式:(X+Y)*(X+Y+2XY)+(XY+1)*(XY-1)
化简x^-y^/x^-2xy+y^
.(x+y-2)(x+y-2xy)+(xy-1)^2
化简 2(xy-xy²+3)-(-4xy²+xy-1) 其中,x等于--4,y等于-3
化简3x^2y-[2xy^2-2(xy-3/2x^2y)+xy]+3xy^2
5x^2y-3xy^2+4xy-14xy^2+4xy-2x^2y(化简)
5xy^2-{2x^y-[3xy^2-(xy^2-2x^2y)]/(-1/2xy)}
(xy-x²)÷(x²-2xy+y²/xy)×(x-y/x²)
x-y/x²÷x²-2xy+y²/xy*(xy-x²)
(x+y)(x-1)-xy-y^2 怎么因式分解?
(-2x)²×(xy+y²)-5x(x-y)×xy化简.
(x*x-2xy)*9x*x-(9xy*y*y-12x*x*x*x*y*y)/3xy,其中x=1,y=-1 化简 帮个忙,
化简:[4xy(x-y)^-1 + (xy^-1 - x^-1y)/(x^-1 + y^-1)] / (x+y)^2
x^2y-2xy+y化简
x²-y²+5x+3y+4(x+y-2xy)(x+y-z)+(xy-1)²
(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)